Immunotherapy of Human Papilloma Virus Induced Disease - van der Burg, Sjoerd H (Bentham Open, 2012)
Immunotherapy is the generic name for treatment modalities aiming to reinforce the immune system against diseases in which the immune system plays a role. The design of an optimal immunotherapeutic treatment against chronic viruses and associated diseases requires a detailed understanding of the interactions between the target virus and its host, in order to define the specific strategies that may have the best chance to deliver success at each stage of disease. Recently, a first series of successes was reported for the immunotherapy of Human Papilloma Virus (HPV)-induced premalignant diseases but there is definitely room for improvement. Here I discuss a number of topics that in my opinion require more study as the answers to these questions allows us to better understand the underlying mechanisms of disease and as such to tailor treatment.